Policy Priorities for Disseminating Biopesticide in Chili Farmers - Wahyu Ridwan Nanta; Suryo Wiyono; Yayi Munara Kusumah (Institut Pertanian Bogor, 2025)
Controlling pests and diseases of chili plants still relies on synthetic chemical pesticides, which have negative effects on agroecosystems. Biopesticides can be used as alternatives to synthetic pesticides. The use of biopesticides in Indonesia is still low, and popularization efforts are required. The government plays a role in determining policies that encourage the popularization of biopesticides. This study aimed to determine policy priorities for the popularization of biopesticides for chili farmers. Policy priorities are determined using the analytical hierarchy process (AHP) method, which allows the identification of priority criteria and priority sub-criteria. The current policy on crop protection is insufficient to encourage the popularization of biopesticides. Low commercialization and government programs that are not yet massive are indications of the low use of biopesticides. The AHP results showed that the criteria for knowledge about biopesticides are policies that must be prioritized, where the sub-criteria of the level of intensity and quality of extension are the top priorities. The effectiveness and efficiency policy criteria need to prioritize the effectiveness of sub-criteria in controlling pests and diseases over the efficiency of use, preservation of natural enemies, and product quality, while the ease of obtaining products is the main factor in prioritizing the availability and affordability criteria. Keywords: analytical hierarchy process, AHP, biopesticide, farmers, IPM, policy